Developing a constitutive approach for peats from laboratory data. (September 2021) - Jommi, C.; Chao, C.Y.; Muraro, S.; Zhao, H.F.
Abstract: Recent research effort carried out at Delft University of Technology to improve the experimental knowledge and develop a comprehensive modelling approach for fibrous organic soils is summarised. Experimental results and numerical analyses are combined to discuss some contradictory results which have delayed advanced characterisation of peats. Part of the apparent inconsistencies commonly found in the literature is due to the influence of the testing apparatus, including rough platens and membrane restraint, which inhibit homogenous deformation modes and alter the response of the samples compared to the true material behaviour. The consequences of non-homogenous deformation are particularly relevant on peats due to the unique combination of their exceptionally low stiffness and high strength. An elastic–plastic constitutive framework was developed starting from repeatable reconstituted samples of peats, taking care of reducing end restraint to a large extent in the experimental setup. The results suggested that an elastic–plastic model for peats should include a non-associated flow rule and a mixed volumetric–deviatoric hardening law. The role played by different fibres at the laboratory scale is discussed, and the additional reinforcement offered by bigger fibres on the observed behaviour of natural peats is addressed. Highlights: Peats are not weird. Peats are composite materials. Some apparent contradictory results can be explained by the influence of the setup. Peats obey a non-associated flow rule and a volumetric-deviatoric hardening law. Natural peats require an explicit description of the kinematics of big fibres.